The use of Different Schemes of Antiviral Therapy of Acute Respiratory Viral Infection in Children - A. L. Zaplatnikov; E. G. Kondyurina; T. N. Elkina; O. A. Gribanova; N. I. Pirozhkova; G. A. Mingalimova; I. O. Tyuleneva (LLC "Diagnostics and Vaccines", 2015)
To optimize selection of antiviral agents for children in routine practice of ARVI management, a double-center, prospective, open-label, randomized study of efficacy and tolerability of schemes including Ergoferon, Cagocel, Arbidol in children > 3 years was performed throughout two epidemic seasons (fall 2012 - spring 2014). In total 152 children with ARVI symptoms lasting for no more than 48 hours were randomized into 3 groups, i.e. Ergoferon (group E, n = 67), Cagocel (group C, n = 40), Arbidol (group A, n = 45). At visits 2 and 3 proportion of children with normalized body temperature (primary criterion) and intensity of intoxication and catarrhal syndrome were evaluated. At visit 3 the following parameters were measured: efficacy index (efficacy and tolerability assessment by the doctor using CGI scale) and evaluation of safety and tolerability of the study drug by parents/representatives of the child; incidence of medical product prescriptions was recorded, i.e. the total number of prescriptions per group, incidence and duration of administration of individual groups of agents. To analyze and evaluate the data obtained, conventional methods of parametric and non-parametric statistics were applied. Groups C and A were not statistically different in baseline characteristics and throughout efficacy criteria assessment. A new group 2 (n=85) was generated out of these groups for further analysis. At visit 2 group 1 and group 2 showed normalization in morning and evening body temperature in 76% and 79% in group 1, respectively, vs. 73% and 79% - in group 2 (2, p > 0.05). 100% subjects in group 1 and 98% - in group 2 did not have intoxication signs, or the rank value of mild intoxication did not exceed 1 (mild). Proportion of subjects with mild catarrhal syndrome at rank 2-3 in group 1 vs. baseline reduced from 15% to 3%, in group 2 - from 18% to 8%. At visit 3, 94% subjects in group 1 and 95% - in group did not show clinical intoxication signs. Almost every one in three children in both groups had catarrhal signs completely resolved by the end of the treatment, in 70% and 65% cases in groups 1 and 2 severity of catarrhal syndrome did not exceed rank 1 (2, p > 0.05). No adverse effects associated with the study scheme components have been reported during the study. Efficacy and tolerability evaluation by the doctors using CGI in group 1 was 3.37 ± 0.65 (M ± SD, 95% CI 3.22-3.53) vs. 3.23 ± 0.77 (M ± SD, 95%CI 3.08-3.39) in group 2 (Т-test, p = 0.38). In group 1 maximum rating (4 scores) was assigned by the doctors in 46%, minimum one (2 scores) - in 9%, while in group 2 the equivalent proportions were 40% and 16%, respectively (p = 0.44 for maximum score and p = 0.17 for minimum score). Therapeutic efficacy evaluation by  parents in group 1 was 3.73 ± 0.57 (M ± SD, 95% CI 3.59-3.87) vs. 3.35 ± 0.72 (M ± SD, 95%CI 3.20-3.50) in group 2; Т-test, p = 0.04. According to frequency assessment, positive scoring (4-5 scores) was more prevalent among parents in group 1: 71% vs. 44% (group 2), 2 test, p = 0.001, minimum scoring (2 scores) was less common in group 1: 1.5% vs. 12% (group 2),?2 test, p = 0.02. Evaluation of therapeutic tolerability by parents in group 1 (4.04 ± 0.53, 95%CI 3.91-4.18) was higher as compared to group 2 (3.82 ± 0.53, 95%CI 3.71-3.93); Т-test, p = 0.01. Maximum scoring (5 scores) was obtained in group 1 in 16% cases, in group 2 - 6% (2 test, p = 0.03). Analysis of additional drug prescriptions revealed that 3.6 ± 1.2 prescriptions have been made on average in group 1 vs. 5.0 ± 1.2 in group 2 (Т-test, р = 0.01). Proportion of children receiving more than 5 drugs was 18% in group 1 vs. 32% in group 2 (2 test, p = 0.05). Seven drugs were given to 3% children in group 1 and 12% - in group 2 (exact Fisher's test, p = 0.067). Duration of therapy with H1-histamine blockers in group 1 was 5 days (Me: 5.0 (5.0; 6.0) vs. 8.5 days (Me: 8.5 (7.5; 10.0) in group 2 (U-test, р = 0.006). Therefore, comparable clinical efficacy and tolerability of anti-ARVI therapeutic schemes were revealed in children using Ergoferon, Cagocel and Arbidol. At that Ergoferon group showed higher therapeutic quality scoring (efficacy and tolerability), both according to the doctors (CGI scale) and parents. Reduced number of prescriptions and duration of drug therapy in Ergoferon group for ARVI management were revealed.